Changes in body composition and activity levels of a Division-1 football team during COVID-19 - Cholewinski, M. C.; Buzzard, J. A.; Gordon, Q.; Ross, R.; Funderburk, L.; Galucci, A. (Journal of Exercise and Nutrition, 2021)
Introduction: The effect that training cessation due to the COVID-19 pandemic had on a Division-1 football team`s activity levels and body composition. Methods: Dual-energy X-ray absorptiometry (DXA) were taken in February and upon return to campus during the athletic department`s normal medical screenings. To measure the athletes` activity during the suspended activity period the validated Modifiable Activity Questionnaire (MAQ) was given to the athletes to confidentially complete. Along with the MAQ were two rating of perceived exertion (RPE) scales that corresponded to cardiovascular work or strength work. Results: Strength/Weight training was the most frequent activity recorded during this time (n = 56) with an average of 16.14 sessions (SD = 6.92) per-month. Significant fat mass increased and lean mass losses were seen in both linemen/non-linemen. Frequency of training was a significant predictor of lean mass loss in non-linemen but not linemen. Conclusions: During the COVID-19 suspension of activities the athletes saw significant decreases in fat free mass with increases in fat mass and body fat percentage. Although, strength/weight training was the most frequently reported activity undertaken during this time it was still not sufficient to maintain the fat free mass of the athletes.